NISBAH KELAMIN DAN UKURAN PERTAMA KALI MATANG GONAD IKAN LAYANG DELES (Decapterusmacrosoma BLEEKER, 1841) DI PERAIRAN TELUK BONE, SULAWESI SELATAN - Dahlan, Muh. Arifin; Andy Omar, Sharifuddin Bin; Tresnati, Joeharnani; Umar, Moh Tauhid; Nur, Muhammad (Hasanuddin University, 2015)
This research was conducted to investigate the sex ratio and the first gonadal maturity size of mackerel fish(Decapterus macrosomas Bleeker 1841). Samples were taken from June to October 2013 in the sub-district ofPanyula, District of East Riattang, in Bone region. Sample analysis was conducted at the Fisheries biologylaboratory, Department of Fisheries, Hasanuddin University, Makassar. Sex ratio was analyzed by using chiquadrat-testwhereas the first gonadal maturity size was obtained from the first size of the third-gonadal-maturitystage. There were 782 fish collected with male to female ratio 1,02:1,00. Statistically, the sex ratio from Bone waterswas 1:1, in other words, it is still in a balance condition. The male fish reached gonadal maturity stage at the size of195 mm, whereas the female at 210 mm. Keywords: sex ratio, gonadal maturity size, Mackarel fish, Bone strait.